Why do financial market experts misperceive future monetary policy decisions? - Sandra Schmidt; Dieter Nautz (Verein für Socialpolitik, 2010)
This paper investigates whether financial market experts correctly perceive the reaction function of the European Central Bank (ECB) with respect to macroeconomic variables. Using survey expectations of financial market experts, we explain the individual interest rate forecast errors within the theoretical context of a Taylor rule. The empirical findings show that the financial market experts systematically misperceive the ECB's Taylor rule parameters. More precisely, their estimate of the inflation parameter is higher than the ECB's inflation parameter but becomes more accurate after an ECB 'clarification' about its monetary policy strategy in May 2003. The estimation results further suggest that the disagreement among experts about the ECB's reaction to inflation has not increased since the financial market crisis.
Keywords: E58; E47; C23; 330; Central bank communication; Interest rate forecasts; Survey expectations; Panel random coeffcient model